Effect of video-assisted mindfulness deep breathing among collegiate athletes with chronic ankle instability - Vinodhkumar, Ramalingam (2022)
Chronic ankle instability (CAI) is the most common injury in sportsmen, causing psychological stress from doubting their performance. Mindfulness intervention on pain management established in numerous studies, but intervention with video-assisted deep breathing during injury is still scarce. The present study aimed to investigate the effects of 3-min video-assisted mindfulness deep breathing (VAMDB) through neurophysiological changes on pain management in addition to conventional physiotherapy (CP) among CAI. The study recruited 23 collegiate athletes without CAI to the healthy control group, and 30 collegiate athletes with CAI randomly assigned to the experimental group (VAMDB+CP) and control group (CP only). The effectiveness of interventions assessed at three intervals using Cumberland ankle instability tool, functional ankle instability index, visual analogue score, brief pain inventory, mindful attention awareness scale, Oxford happiness questionnaire, Y -balance, and EEG. A 14-channel EEG employed as a novel bio-indicator of pain. Independent t-test and two-way repeated-measures ANOVA were applied to the significant level (p<0.05). Pearson's correlation used to report the association of EEG with pain. CAI participants reported a significant increase (p<0.001) in pain intensity and interference, along with a significant decrease (p=0.001) in dynamic balance and happiness scores compared with health control group. Further, the increase in pain among CAI participants showed a significant decrease (p<0.05) in EEG response and a negative association with alpha, beta, and theta waves over occipital and left temporal regions. After exposed to 6-weeks of intervention and 6- weeks of follow-up, CAI participants in experimental and control groups reported a significant improvement (p<0.05) over the time interval in pain, balance, and happiness. However, the mindful attention showed a significant difference in the timexgroup (p=0.001), with an increased attention score in the experimental group. Further, the increase in mean occipital alpha found to be a sensitive indicator of improvement in male CAI participants.